1998
DOI: 10.1046/j.1365-2044.1998.00633.x
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Prophylactic anti‐emetic therapy with granisetron, droperidol and metoclopramide in female patients undergoing middle ear surgery

Abstract: SummaryThe efficacy of granisetron, droperidol and metoclopramide for the prevention of postoperative nausea and vomiting in female patients undergoing middle ear surgery was compared. In a randomised, double-blind study, 180 patients received granisetron 40 mg.kg ¹1, droperidol 20 mg.kg ¹1 or metoclopramide 0.2 mg.kg ¹1 given intravenously immediately before induction of anaesthesia (n ¼ 60 for each). A standardised general anaesthetic technique was employed throughout. A complete response, defined as no post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…Our study coincides with the findings of various studies of Fuji et al [6,7,[10][11][12] where complete response rate were between 78 and 86% with varying doses of granisetron having the PONV 14-22%. PONV was much less in our study although we had used granisetron in lesser dose as compared to these studies.…”
Section: Discussionsupporting
confidence: 92%
“…Our study coincides with the findings of various studies of Fuji et al [6,7,[10][11][12] where complete response rate were between 78 and 86% with varying doses of granisetron having the PONV 14-22%. PONV was much less in our study although we had used granisetron in lesser dose as compared to these studies.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of patients in our study received droperidol. Other studies 10 have reported rates of 42% for PONV when droperidol is used in a preemptive fashion, a rate similar to the 50% we observed in this study. Use of prophylactic antiemetic drugs, including 5-HT 3 receptor antagonists, seems to be ineffective in patients with a history of motion sickness or previous PONV.…”
Section: Commentsupporting
confidence: 90%
“…Despite the higher dose of metoclopramide (20 mg), no patient in our study showed such undesirable effects. Some authors reported on a lower antiemetic potency of metoclopramide compared with the 5‐HT 3 antagonists ondansetron and granisetron, respectively [26–28]. Others found no advantage of 5‐HT 3 antagonists compared with metoclopramide [21].…”
Section: Discussionmentioning
confidence: 99%